Peran Account Executive dan Data Executive dalam Kampanye “Tilik Jiwa” dalam Meningkatkan Awareness dan Partisipasi Layanan Skrining Kesehatan Mental oleh Dinas Kesehatan Kota Semarang - Nailahsana Rafifah Putri; Nurul Hasfi (Interaksi Online, 2026)
The high prevalence of mental health disorders in society has become a significant publichealth concern. On the other hand, public awareness and participation in mental healthscreening services provided by the Semarang City Health Office remain relatively low.Therefore, an effective communication strategy is required to increase awareness andencourage the public to utilize mental health screening services. This project was designedusing a social marketing approach through the “Tilik Jiwa” campaign targeting youngproductive age groups, particularly university students and early-career workers in SemarangCity. The campaign strategy was implemented through various communication activities,including mental health screening events, educational roadshows, and the use of social mediaas an information dissemination platform. In its implementation, the Account Executive actedas the liaison between the implementation team and the client, namely the Semarang CityHealth Office, while the Data Executive was responsible for conducting research andprocessing the data required for campaign planning and evaluation. The results of thecampaign indicate an increase of 87.79 percentage points in awareness, 89.33 percentagepoints in knowledge, and a decrease in stigma toward mental health screening services to12.3%. Furthermore, the Tilik Jiwa campaign successfully increased overall participation by36% or 86 participants in mental health screening activities.